Pemahaman Guru terhadap Implementasi Penguatan Pendidikan Karakter Peserta Didik di Satuan PAUD - Nor Amalia Abdiah (AL-ULUM | JURNAL PENDIDIKAN DAN PENGAJARAN, 2023)
Building character in schools can be done well if teachers and educators understand the value of education. The understanding of educators in strengthening character education helps them design effective learning strategies and pay special attention to the development of student's character. This study aims to explain the extent to which teachers understand the implementation of strengthening character education in PAUD units with a qualitative approach. The strengthening of character education implemented in PAUD units is not going well due to the teacher's incomplete understanding of guidebooks from the Ministry of Education and Culture Directorate General of Early Childhood Education and Community Education Directorate of Early Childhood Education in 2019. This study founds that the subjects needed assistance in implementing a strengthening character education program in PAUD units.